Tradycje zinstytucjonalizowanego poradnictwa psychologiczno-pedagogicznego w Wielkopolsce przed rokiem 1945 - Knocińska, Anna (Biuletyn Historii Wychowania, 2012)
The main aim of the dissertation is to present the institutionalized traditions of psychological and pedagogical counseling in Great Poland before 1945. It brings closer the socio-political situation as well as the conditions resulting from the development of the social sciences that influenced the beginning of the first counseling institutions in Great Poland and in the whole country. It also shows the individual counseling posts that started functioning in Poznan in 1945. The outbreak of the World War II interrupted the development of psychological and pedagogical counseling in Great Poland.